Eksplorasi Keterampilan Berpikir Kritis dengan Desain Lembar Kerja Project-Based Learning - Rezkie Zulkarnain (Departement of Mathematics Education, 2022)
Critical thinking skills as 21st Century Education paradigm requires educators to integrate the latest ideas in learning. This research was conducted to find information and knowledge about students' critical thinking skills using Project Based Learning (PjBL) Worksheets. With an analytical review, researchers can classify the problems faced by students in their critical thinking efforts, then determine the logical relationship of the problems that occur. This study used a qualitative method with a descriptive analysis approach with a data source of 120 students divided into groups in the Research Methodology course. The results showed that the PjBL Worksheet supports students' critical thinking skills in gathering information, describing problems, evaluating project results, and solving problems that are the project's target. This can be seen in the results of observing group activities and the project assessment rubric that according to indicators of students' thinking skills, shows that most study groups are able to analyze problems, actively seek references regarding the project to be made and its benefits, actively complete the design, and show the best possible results of the project.